Electrical properties and microstructure of magnetoresistive ( (x = 0.0, 0.05, 0.15 and 0.3) - Ewe, L.S.; Hamid, N.A.; Abd-Shukor, R. (Universiti Kebangsaan Malaysia, 2006)
The insulator-metal transition temperature, Tim of (x = 0.0, 0.05, 0.15 and 0.3) was studied during warming and cooling between 50 K to 300 K. The results showed that Tim of shifted to a higher temperature as Sr was substituted for La. Scanning electron micrographs showed that the average grain size is in the range of 0.6 µm - 1.4 µm. Grain boundaries are almost completely revealed for x = 0.3. X-Ray powder diffraction patterns showed cubic structure (space group Pm-3m) and contain no secondary phases.